The persistence of anguish: memory, absence, and voice in colombian video art (2014)
It seems that there is no place foraesthetics in a conflictive contextsuch as the Colombian one;however, local artists have insistedon hinting at those aspects of thereal that we turn our backs on inorder to protect ourselves. In thisorder of ideas, the article highlightsthe ethical nature of a series ofColombian video art works that“make a statement” regarding thesocio-cultural conditions in whichthey arose. Appealing to memory,absence, and voice, it seems thatthese works seek to startle andproduce anguish in their viewers bypresenting an abundance of banaltexts and images offered by the media(including the already famoussignifier, “post-conflict”), whichdistract us from the horrors of war.